Snow White and the Seven Dwarfs [videorecording (Blu-Ray + DVD)] - Grimm, Wilhelm, 1786-1859; Grimm, Jacob, 1785-1863 (Disney DVD., 2016)
The beautiful and kindhearted princess Snow White charms every creature in the kingdom except one, the Queen, her jealous stepmother. When the Magic Mirror proclaims Snow White as the fairest one of all, she must flee into the forest. There, she befriends the lovable seven dwarfs, Doc, Sneezy, Grumpy, Happy, Bashful, Sleepy and Dopey. The Queen finds Snow White and tricks her with an enchanted apple. Only the magic of true love's kiss can save her.